La violencia intrafamiliar y relación con los niveles de autoestima, en los estudiantes de 12 a 15 años de la Escuela Fiscal de Educación Básica Superior José Ingenieros, de la ciudad de Loja. - Carchipulla Garrochamba, Liliana Maribel (2017)
The herein research focused in: “Family Violence and its relation with Self-esteem Levels in students aged between 12 and 15, in the government basic highschool “José Ingenieros in the city of Loja. The specific objectives were to detect cases of Violence and to identify Self-esteem levels.The study conducted was quali-quantitative, descriptive, correlational, cross-sectional, in which a sample of 154 students, victims of family Violence was selected. The instruments used were: 1) Family Violence Questionnaire, 2) Rosemberg´s Self-esteem Scale. According to the data obtained: 41,0% of students showed first degree of Violence, 26,7%, having average self-esteem. 28,6 % of students, who presented severe Violence have a predominance of low self-esteem with 23,8 %. To end up, 3,8% of the studied population with dangerous Violence shows low self-esteem values with 3,3 %, showing there the is indeed a relation between family Violence and self-esteem levels. Finally, a Psycho - therapeutic proposal was designed with the aim of Improving the Life Quality of Students and to Diminish the levels of Family Violence. Kew words: family Violence, self - esteem